On the decomposition mechanism of propanal: rate constants evaluation and kinetic simulations - Della Libera, Andrea; Di Teodoro, Maristella; Pelucchi, Matteo; Cavallotti, Carlo (Theoretical chemistry accounts, 2023)
The reactivity of aldehydes has been the subject of considerable interest in chemical kinetics, with propanal often chosen as the representative species. Despite its relevance, the reactivity of propanal is currently estimated from analogy and fitting of experimental data measured in limited temperature and pressure ranges, while the few literature theoretical studies have focused more on the exploration the potential energy surface (PES) than on the estimation of rate constants. The purpose of this work is to reinvestigate the propanal decomposition kinetics using the ab initio transition state theory based master equation approach with the intent of: (1) Determining accurate rate constants of key reaction channels; (2) Updating and validating an existing kinetic model by simulating available experimental data on propanal pyrolysis. It is found that propanal decomposition at the initial stages of pyrolysis occurs through four unimolecular barrierless reactions to form CHO + C 2 H 5 , CH 2 CHO + CH 3 , CH 3 CHCHO + H, and CH 3 CH 2 CO + H, and a termolecular pathway leading to the formation of C 2 H 4 + CO + H 2 . High pressure rate constants were determined for each barrierless reaction channel using Variable Reaction Coordinate Transition State Theory and used to estimate phenomenological temperature and pressure dependent channel specific rate constants integrating the 1 dimensional master equation over the whole PES. The decomposition rate constants so determined are in agreement with the few available experimental data and significantly faster than previous literature estimates. The estimated kinetic parameters were finally implemented into the CRECK kinetic mechanism, leading to an improved agreement with shock tube pyrolysis data from the literature.